جادوئی حقیقت نگاری : تعریف ، عناصر اور طریقہ کار (تحقیقی مطالعہ) - فضل کبیر; مسرور حسین; سدرہ صادق (Khayaban - خیابان, 2024)
Abstract Magical realism is being used as major tool and technique in fiction explaining postmodern and/or depressed colonial settings. The technique aims to relate socio-political situation through unnatural events and elements as natural. This article is an attempt to explain its context as it is understood and utilized by Urdu literature writers and critics. As this technique mainly involves mixing elements of factual and imaginary world, and authors displays self-proclaimed picture of time, the Urdu context make this richer experience through tradition of mythology and their depiction in literature. The method of this technique includes pluralism, hybridity, authorial reticence and marvelous reality, and this article documents the understanding of Urdu authors and critics of these themes.